Does the Nature of the Crisis Matter? A Study of Global Bank Performance during a Credit Crisis, The Debt Crisis &; Health Crisis - Vermaak, Kelly (Department of Finance and Tax, 2023)
This study examined the global performance of banks during the Global Financial Crisis (GFC), the sovereign debt crisis, and COVID-19 crisis. An ordinary least squares (OLS) multiple regression model was used to observe the influence of bank specific, macroeconomic and industry related variables on global bank performance. Buy-hold-abnormal-returns (BHAR) were used as a measure of performance to assess whether the nature of the crisis mattered. A sample period of June 2007 to December 2008, May 2011 to December 2011, and 11 January 2020 to 31 May 2020 were used to represent the GFC, sovereign debt crisis, and COVID-19 crisis, respectively. Higher liquidity, loans, beta, and idiosyncratic volatility as well as a lower credit-loss ratio explained the poor performance of banks during the GFC. The negative spillover effects from the GFC significantly hindered banks' lending capacity and ability to obtain funding from the short-term market during subsequent crises. This meant lending and loans had no influence on performance during the sovereign debt crisis, evident by the insignificant relationship found. Unlike the finding for the GFC and COVID-19 crisis, both beta and idiosyncratic risk were unable to explain performance during the sovereign debt crisis. Similar to the GFC, lower loans, liquidity and credit-loss ratio helped banks achieve better returns, while greater exposure to systematic and idiosyncratic risk led to poorer performance during the COVID-19 crisis. The study further found that banks were more susceptible to the COVID-19 crisis relative to the credit crisis. Furthermore, banks in countries with a high GDP per capita and current account balance witnessed better performance during the COVID-19 crisis. Policy support and the release of Basel III, post the GFC, significantly aided in bank resilience and performance during crisis periods. However, this study found no relationship between bank share price performance and bank capital. During the COVID-19 crisis only, banks with more tangible equity earned greater returns. The policy implications of the findings highlighted how responses from previous crises ensured the financial stability of the financial system and its ability to withstand these shocks. Overall, the difference in findings across each crisis suggested that the nature of the crisis matters. Knowing the nature of the crisis and factors which influenced that particular type of crisis could help inform banks and authorities on when and how to take early precautions in the event of an approaching crisis.